Organ-Specific vs. Patient Risk-Specific Tube Current Modulation in Thorax CT Scans Covering the Female Breast - Klein, Laura; Enzmann, Lucia; Byl, Achim; Liu, Chang; Sawall, Stefan; Maier, Andreas; Maier, Joscha; Lell, Michael; Kachelrieß, Marc (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
An important goal in modern CT imaging is reducing the dose delivered to patients especially to risk-relevant organs. This work compares the clinically applied dose reduction techniques mAs-minimizing tube current modulation (mAsTCM) and a typical organ-specific TCM (osTCM, here: X-Care, Siemens Healthcare) with a novel radiation risk-minimizing tube current modulation (riskTCM) with a focus on the dose delivered to the female breast. The mAsTCM minimizes the mAs product as a surrogate parameter for the patient dose but does not consider the different organs' risks. In contrast, osTCM aims to minimize the dose delivered to the female breast by reducing the tube current for anterior projections. The riskTCM minimizes the patient risk by minimizing the effective dose to the patient, which is done by taking accounting for the organ doses. In this study, the dose reduction effect of the TCM techniques is compared by simulations based on clinical CT scans. Thereby, riskTCM reduces the effective dose by up to 35% in comparison to mAsTCM, and by up to 30% in comparison to osTCM depending on the anatomical region and the patient.
CRIS-Team Scopus Importer:2022-11-25
Keywords: chest imaging; CT; dose reduction; tube current modulation